Countermovement jumps and acute to chronic workload ratios in low, moderate, and high jump load groups throughout a Division I volleyball season - Sanders, G. J.; Skodinski, S.; Cabarkapa, D. V.; Howard, M.; Cabarkapa, D.; Kollock, R. O.; Peacock, C. A. (The Journal of Strength and Conditioning Research, 2024)
The purpose of the study was to evaluate the effects of low, moderate, and high jump loads on the acute to chronic workload ratio (ACWR) and neuromuscular fatigue throughout a Division I volleyball season. Twelve female volleyball athletes were monitored throughout a competitive season to track daily jump loads and measure neuromuscular fatigue based on twice-weekly countermovement jumps (CMJs) using a dual force plate. Jump loads were categorized into thirds (low, moderate, high-volume) to assess changes in neuromuscular fatigue, and a secondary evaluation examined differences in the ACWR. The results of this study were statistically significant with a p = 0.05. The Wilks Lambda test in the multivariate analysis of variance found there were main effects for low, moderate, and high jump load groups (F = 50.498, p < 0.001), weeks (F = 3.136, p < 0.001), and significant group by week interactions (F = 1.751, p < 0.001) for jump loads and CMJ test results. There was no main effect of week for ACWR (F = 0.634, p = 0.849), and although statistically different, there were minimal changes in the ACWR between groups. There were significant variations in jump loads and CMJ performance between low, moderate, and high jump load groups across a 16-week season, most notably after week 5. In addition, the data highlight the limitations of the ACWR when detecting changes in athlete fatigue throughout the season.